2001
DOI: 10.1002/1097-0142(20011001)92:7<1896::aid-cncr1707>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of pretreatment serum levels of HER-2/neu oncoprotein as a prognostic and predictive factor in patients with advanced nonsmall cell lung carcinoma

Abstract: Reasoning about legal cases is a complex skill that imposes a high working memory load, especially for novice students. Not only do novices lack necessary conceptual knowledge, searching through the information sources that are used during reasoning can also be assumed to impose a high additional working memory load that does not contribute to learning. Therefore, this study investigated the effects of supporting novice law students' learning by (a) providing the meaning of important concepts in the case and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…They concluded that serum measurement of these markers is a promising noninvasive technique which needs correlation with other methods of determination, measurement at different chronological points during disease evolution to explore its full potential. Ardizzoni and coworkers [36] found that high pretreatment serum levels of HER-2/neu oncoprotein are associated with an adverse prognostic impact on survival in patients with locally advanced or metastatic nonsmall cell lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that serum measurement of these markers is a promising noninvasive technique which needs correlation with other methods of determination, measurement at different chronological points during disease evolution to explore its full potential. Ardizzoni and coworkers [36] found that high pretreatment serum levels of HER-2/neu oncoprotein are associated with an adverse prognostic impact on survival in patients with locally advanced or metastatic nonsmall cell lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a previous study on serum HER2 of advanced NSCLC patients. Ardizzoni et al 27 designed a study to assess the potential value of measuring serum levels of HER-2/neu oncoprotein in predicting response to treatment and survival in patients with locally advanced and metastatic non-small cell lung carcinoma. They used ELISA to determine serum HER2 concentration in peripheral blood of 86 newly-diagnosed IIIB/IV NSCLC patients undergoing platinum-based standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, elevated pre-treatment serum levels of HER2 protein have also been associated with shorter survival. In one report of 84 patients with stage III or IV squamous and nonsquamous histology NSCLC, the median survival of patients with serum HER2 levels greater than 73 fm/mL was significantly shorter than for those with lower levels (7.1 months versus 10.9 months) [80].…”
Section: Prognosis In Nsclcmentioning
confidence: 96%